Development of Novel Pyridine-Thiazole Hybrid Molecules as Potential Anticancer Agents - Iryna Ivasechko; Ihor Yushyn; Piotr Roszczenko; Julia Senkiv; Nataliya Finiuk; Danylo Lesyk; Serhii Holota; Robert Czarnomysy; Olga Klyuchivska; Dmytro Khyluk; Nataliya Kashchak; Andrzej Gzella; et al. (Molecules, 2022)
Novel pyridine-thiazole hybrid molecules were synthesized and subjected to physico-chemical characterization and screening of their cytotoxic action towards a panel of cell lines derived from different types of tumors (carcinomas of colon, breast, and lung, glioblastoma and leukemia), and normal human keratinocytes, for comparison. High antiproliferative activity of the 3-(2-fluorophenyl)-1-[4-methyl-2-(pyridin-2-ylamino)-thiazol-5-yl]-propenone 3 and 4-(2-{1-(2-fluorophenyl)-3-[4-methyl-2-(pyridin-2-ylamino)-thiazol-5-yl]-3-oxopropylsulfanyl}-acetylamino)-benzoic acid ethyl ester 4 was revealed. The IC50 of the compound 3 in HL-60 cells of the acute human promyelocytic leukemia was 0.57 µM, while in the pseudo-normal human cell lines, the IC50 of this compound was >50 µM, which suggests that the compounds 3 and 4 might be perspective anticancer agents. The detected selectivity of the derivatives 3 and 4 for cancer cell lines inspired us to study the mechanisms of their cytotoxic action. It was shown that preincubation of tumor cells with Fluzaparib (inhibitor of PARP1) reduced the cytotoxic activity of the derivatives 3 and 4 by more than twice. The ability of these compounds to affect DNA nativity and cause changes in nucleus morphology allows for the suggestion that the mechanism of action of the novel pyridine-thiazole derivatives might be related to inducing the genetic instability in tumor cells.